Identification of Candidate Adaxial–Abaxial-Related Genes Regulating Petal Expansion During Flower Opening in Rosa chinensis “Old Blush” - Han, Yu; Yong, Xue; Yu, Jiayao; Cheng, Tangren; Wang, Jia; Yang, Weiru; Pan, Huitang; Zhang, Qixiang (Frontiers in Plant Science, 2019)
Petal expansion is the main process by which flower opening occurs in roses (Rosa chinensis). While the regulation of leaf expansion has been extensively studied, little is known about the mechanisms controlling petal expansion. The regulation of leaf dorsoventral (adaxial–abaxial) polarity is important for blade expansion and morphogenesis, but the mechanisms involved adaxial-abaxial regulation in petals are unknown. We found that auxin, a key hormonal regulator of leaf adaxial–abaxial patterning, is unevenly distributed in rose petals. The transcriptomes of the adaxial and abaxial petal tissues were sequenced at three developmental stages during flower opening. Genes that were differentially expressed between the two tissues were filtered for those known to be involved in petal expansion and phytohormone biosynthesis, transport, and signaling, revealing potential roles in petal expansion, especially auxin pathway genes. Using a weighted gene coexpression network analysis (WGCNA), we identified two gene modules that may involve in adaxial–abaxial regulation, 21 and five hub genes have been found respectively. The qRT-PCR validation results were consistent with the RNA-seq data. Based on these findings, we propose a simple network of adaxial–abaxial related genes that regulates petal expansion in R. chinensis ‘Old Blush’. For the first time, we report the adaxial–abaxial transcriptional changes that occur during petal expansion, providing a reference for the study of the regulation of polarity in plant development.